Vitamin D3 oral rinsing reduces salivary SARS-CoV-2 antigen detectability: a clinical trial with public health implications - Sarah M. Nizar Feteih; Emily L. G. Heaphy; Amjad Aljagthmi; Abdullah Abumdaini; Daniyah Bayumi; Ghadeer Albishi; Ashraf Dada (Frontiers in Oral Health, 2026)
Objectives To determine whether a Vitamin D 3 oral rinse alters the performance of saliva-based SARS-CoV-2 rapid antigen testing (RAT) and assess its potential implications for infectious disease screening and public health surveillance. Methods In this prospective, paired-sample, single-blind clinical trial, 25 adults with laboratory-confirmed SARS-CoV-2 infection provided saliva immediately before and after a standardized one-minute Vitamin D₃ oral rinse (50 paired specimens). Samples were analyzed in parallel by saliva RAT and rapid RT-PCR under blinded conditions. Results The oral rinse converted 68% (17/25) of paired specimens from RAT-positive to RAT-negative, reducing antigen positivity from 54.2% to 32.0% ( p = 0.0016). In contrast, RT-PCR positivity remained largely preserved (96.0% vs. 88.0%), with no significant change in mean Ct values (28.1 ± 5.9 vs. 29.4 ± 5.1; p = 0.1785). Strong concordance between paired RT-PCR samples ( ρ = 0.814, p < 0.0001) indicated persistent viral RNA despite reduced antigen detection. Conclusions Vitamin D₃ oral rinsing was associated with reduced detection by saliva-based SARS-CoV-2 RAT while RT-PCR results remained largely preserved. These findings suggest a previously under-recognized pre-analytical variable capable of altering saliva-based antigen detection. Clinical Trial Registration: https://clinicaltrials.gov/study/NCT07068282 , Identifier, NCT07068282.